Comparisons of ground reaction forces between two different 180-degree turning techniques in female cricketers - Laucha, T.; Suwanmana, S.; Srisuwan, N.; Jamkrajang, P.; Limroongreungrat, W. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
Changing direction (COD) particularly a 180-degree turn is a key skill in cricket. Two different techniques, Side-lunge (SL) and sprinting (SP) are commonly performed by cricketers. The aim of this study was to compare ground reaction forces (GRF) differences before turning between the two techniques. Nine Thai national female cricket players volunteered in this study. Participants executed running and 180-deg turning techniques while holding a bat on a track with embedded force platforms. GRFs and contact time (CT) at the three-foot contact events; antepenultimate (AFC), penultimate (PFC), and final (FFC) were analysed. The results showed that all GRFs of SP at AFC are significantly higher than SL (p<0.05). However, GRFs during SL were higher at PFC (p<0.05). This finding revealed different GRFs between two techniques particularly at AFC and PFC.